Diversity and taxonomic revision of methanogens and other archaea in the intestinal tract of terrestrial arthropods - Protasov, Evgenii; Nonoh, James O.; Kästle Silva, Joana M.; Mies, Undine S.; Hervé, Vincent; Dietrich, Carsten; Lang, Kristina; Mikulski, Lena; Platt, Katja; Poehlein, Anja; Köhler-Ramm, Tim; Miambi, Edouard; et al. (Frontiers in Microbiology, 2023)
Methane emission by terrestrial invertebrates is restricted to millipedes, termites, cockroaches, and scarab beetles. The arthropod-associated archaea known to date belong to the orders Methanobacteriales, Methanomassiliicoccales, Methanomicrobiales, and Methanosarcinales, and in a few cases also to non-methanogenic Nitrososphaerales and Bathyarchaeales. However, all major host groups are severely undersampled, and the taxonomy of existing lineages is not well developed. Full-length 16S rRNA gene sequences and genomes of arthropod-associated archaea are scarce, reference databases lack resolution, and the names of many taxa are either not validly published or under-classified and require revision. Here, we investigated the diversity of archaea in a wide range of methane-emitting arthropods, combining phylogenomic analysis of isolates and metagenome-assembled genomes (MAGs) with amplicon sequencing of full-length 16S rRNA genes. Our results allowed us to describe numerous new species in hitherto undescribed taxa among the orders Methanobacteriales (Methanacia, Methanarmilla, Methanobaculum, Methanobinarius, Methanocatella, Methanoflexus, Methanorudis, and Methanovirga, all gen. nova), Methanomicrobiales (Methanofilum and Methanorbis, both gen. nova), Methanosarcinales (Methanofrustulum and Methanolapillus, both gen. nova),(Methanomethylophilaceae